Public relations programs in special libraries in Quezon City - Duñgo, Liezel Celeste M. (1999)
This study investigated the public relations programs of ten special libraries in Quezon City. Specifically, this study: (1) found out the public relations techniques being employed in promoting library collection and services; (2) discovered how much of the total library budget is allocated to public relations programs; (3)determined the library users' opinions on the use of public relations with regard to promoting the library to its actual users and (4) identified the problems related to public relations that are encountered by special librarians.